2014
DOI: 10.1002/adsc.201300960
|View full text |Cite
|
Sign up to set email alerts
|

Laccase and Laccase‐Mediated Systems in the Synthesis of Organic Compounds

Abstract: Laccase, a blue multicopper oxidase, has recently received considerable attention because of its usefulness in oxidizing phenolic and non‐phenolic compounds, as well as its suitability for organic synthesis, environmental pollutant treatment, and other biotechnological applications. This review covers recent studies on the structural properties, occurrence, reaction mechnisms, redox mediators of laccases and their application in organic synthesis procedures, such as dimerization, polymerization, oxidation, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
131
0
5

Year Published

2014
2014
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 230 publications
(137 citation statements)
references
References 310 publications
1
131
0
5
Order By: Relevance
“…As more and more laccases are becoming available,t heir synthetic exploitation is significantly growing, as documented by the numerous patents andl iterature reports. [12] In recent years our group has exploited these biocatalysts,i .e., for the selective oxidation of phenolic derivatives [13] and specifically of phenolic stilbenes. [6,14] Following ap reliminary optimization of the reaction parameters,a20 mM solution of piceid (3,1g dissolved in 140 mL of ab uffered solutionc ontaining 30% v/v MeOH to improve its solubility) waso xidized by the commercially available laccase from Trametes versicolor.T he reactionw as gently shaken at 25 8 8Cf or 2-3 hu ntil the starting material was completely oxidized.…”
Section: Resultsmentioning
confidence: 99%
“…As more and more laccases are becoming available,t heir synthetic exploitation is significantly growing, as documented by the numerous patents andl iterature reports. [12] In recent years our group has exploited these biocatalysts,i .e., for the selective oxidation of phenolic derivatives [13] and specifically of phenolic stilbenes. [6,14] Following ap reliminary optimization of the reaction parameters,a20 mM solution of piceid (3,1g dissolved in 140 mL of ab uffered solutionc ontaining 30% v/v MeOH to improve its solubility) waso xidized by the commercially available laccase from Trametes versicolor.T he reactionw as gently shaken at 25 8 8Cf or 2-3 hu ntil the starting material was completely oxidized.…”
Section: Resultsmentioning
confidence: 99%
“…These oxidases can achieve mild oxidations in aqueous media and are compatible with different chemical oxidants, which has broadened their applicability in many (environmentally-friendly) processes. [23][24][25][26][27] While finding important roles in numerous oxidative transformations, only Rutjes and co-workers have performed a systematic study of these systems applied to the deprotection of amines when PMP group was employed. 22 Herein we have shown that this system can perfectly work for the removal of the benzyl moiety, widely utilized to protect amines and alcohols.…”
Section: Discussionmentioning
confidence: 99%
“…Herein we wish to report our latest results in the development of an efficient N-benzyl deprotection reaction taken advantage of the use of laccases (Scheme 1), [23][24][25][26][27] which are multi-copper enzymes found in a myriad of bacteria, fungi and plants. These oxidases reduce O2 into H2O at the expense of the oxidation of the corresponding substrate.…”
mentioning
confidence: 99%
“…Laccase (p-diphenol: dioxygen oxidoreductase, EC 1.10.3.2) belongs to the family of copper-containing oxidases, which catalyze the 1-electron oxidation of a wide range of inorganic and organic substances, coupled with a 4-electron reduction of oxygen to water [1][2][3][4]. This enzyme is among the most studied redoxases and has been used successfully as a commercial industrial catalyst.…”
Section: Introductionmentioning
confidence: 99%
“…This enzyme is among the most studied redoxases and has been used successfully as a commercial industrial catalyst. Laccase (Lac) has shown many applications in biomedical, biotechnological, and environmental areas such as organic synthesis, wine cork making, teeth whitening, immunoassay analyte labeling, biofuel cells, and biosensors [4][5][6]. Moreover, Lac can also play a major role in bioremediation processes such as dye removal from wastewater [7,8].…”
Section: Introductionmentioning
confidence: 99%